Media and Other Socializing Agents Influence on Male Body-Shaping Behavior: Body Esteem as a Mediator - Hanan, Mian Ahmad (Animo Repository, 2021)
Media and other socializing agents can play an influential role in creating an ideal male body because people live their lives in bodies. The influence of socializing agents on male body-shaping behavior is not widely discussed compared to the female case. This study is investigating whether the moderating role of body esteem between media and sociocultural factors has an impact on male body-shaping behavior. It examines the influence of media images and socializing agents in changing or maintaining that appearance among males. The sociocultural attitudes towards appearance, SATAQ-3 Scale, Rosenberg self-esteem scale, and the body image avoidance questionnaire were used to measure male body shaping behavior among 260 young Pakistani adults (M=22.76; SD=4.99). The findings indicated that media advertisements and family influence are significantly positive, whereas body esteem is negatively related to male body-shaping behavior. However, peers and female partner influence do not make any significant contribution to male body shaping behaviors. Furthermore, body esteem acts as a cause for men to indulge in body-shaping behavior to have a perfect ideal masculine body image.